Optimal allocation of means for trauma prevention using stochastic programming - Sigutė Vakrinienė; Petras Čyras (Lietuvos Matematikos Rinkinys)
Optimal criterion for allocation of means necessary for trauma prevention is proposed. The problem is simulated as a matrix game with random elements.